Maldives Economic Update - Rajatha Wijeweera, Kirthirsri; Kularatne, Chandana; Eymard Fonseka, Daminda; Gomez Ozorio, Camilo (World Bank, Washington, DC, 2014)
The political situation remains in a state of flux in the Maldives, with crucial elections coming up. The presidential elections are scheduled for early September 2013, and the Majlis (parliamentary) elections for April 2014. The fiscal position remains in a precarious situation, with the government cash-flow position considerably weakened. Against this backdrop, the government has resorted to very imprudent means of managing the cash-flow situation: (i) ad-hoc borrowings from the banking and private sectors at high interest rates, (ii) monetizing, and (iii) running huge payment arrears, amounting to over 10 percent of gross domestic product (GDP). Continuation of these measures will likely stoke significant imbalances in the economy. The precarious external situation presents the biggest challenge to the country. The situation has been aggravated by continued high fiscal deficits as well as recent debt settlements. Current gross official reserves are below two months of imports and, in face of increased monetization of the deficits, can deteriorate further. In light of the precarious external situation, external debt sustainability has also become a major concern. Under current trajectories, total external debt obligations are projected to reach over 115 percent of GDP by 2015- a seriously vulnerable situation, given the recent slowdown in tourism, and the susceptibility of the economy to external shocks (such as commodity price hikes).